Meta-analysis of the impact of European Union Structural Funds on regional growth. Issue 6 (3rd June 2017) - Dall'Erba, Sandy; Fang, Fang
ABSTRACT: Meta-analysis of the impact of European Union Structural Funds on regional growth. Regional Studies . This paper offers a meta-regression analysis of the controversial impact of European Union Structural Funds on the growth of the recipient regions. It identifies the factors that explain the heterogeneity in the size of 323 estimates of their impact recorded in 17 econometric studies. Heterogeneity comes from the publication status, the period examined, the control of endogeneity and the presence of several regressors, but not from differences in functional forms.